Kathy McKeown Interviews Bonnie Webber - Bonnie Webber (Computational Linguistics, 2021)
AbstractBecause the 2020 ACL Lifetime Achievement Award presentation could not be done in person, we replaced the usual LTA talk with an interview between Professor Kathy McKeown (Columbia University) and the recipient, Bonnie Webber. The following is an edited version of the interview, with added citations.